Дослідження на поселенні трипільської культури біля с. Небелівка 2009 р. - Чепмен, Дж.; Гейдарська, Б.; Вілліс, Р.; Сван, Н.; Бурдо, Н.Б.; Котова, Н.С.; Беленко, М.; Відейко, М.Ю. (Археологічні дослідження в Україні, 2010)
The Joint British-Ukrainian Archaeological Expedition, in which research officers of Durham University (the Great Britain) and the IA NASU participated, in August 2009 conducted a complex research at the settlement of Trypillya culture of the middle stage (BII) near Nebelivka village of Novoarkhanhelsk Region in Kirovohrad Oblast and the archaeological prospecting on the territory of this region.